An enhanced simulated annealing approach for cylindrical, rectangular mesh and semi-diagonal torus network topologies [electronic resource] - Noraziah Adzhar, 1990-, author (2015)
Thesis (Ph.D (Matematik)) - Universiti Teknologi Malaysia, 2015